2006
DOI: 10.1080/01443610600984412
|View full text |Cite
|
Sign up to set email alerts
|

Probability of early pregnancy loss in women with vaginal bleeding and a singleton live fetus at ultrasound scan

Abstract: Bleeding is a common feature of early pregnancy affecting about one-fifth of pregnant women in the first trimester. The chance of miscarriage after bleeding and a live fetus at scan has not previously been defined precisely. The purpose of this study was to evaluate the outcome of early pregnancies with a viable singleton fetus that had been complicated by bleeding. A prospective study was performed on 370 women with a singleton live fetus who had presented to the early pregnancy assessment clinic (EPAC) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 9 publications
2
20
1
1
Order By: Relevance
“…The miscarriage rate was 83.3, 50 and 24.7% in women who complained of heavy, moderate and light bleeding, respectively. The same was found in another study that showed women who reported moderate or heavy bleeding had more than twice the rate of miscarriage compared to those with light bleeding [8]. More recently, bleeding scores have been shown to be useful variables in the prediction of pregnancy outcome, especially if they are used in combination with ultrasound variables [9,10].…”
Section: Discussionsupporting
confidence: 59%
“…The miscarriage rate was 83.3, 50 and 24.7% in women who complained of heavy, moderate and light bleeding, respectively. The same was found in another study that showed women who reported moderate or heavy bleeding had more than twice the rate of miscarriage compared to those with light bleeding [8]. More recently, bleeding scores have been shown to be useful variables in the prediction of pregnancy outcome, especially if they are used in combination with ultrasound variables [9,10].…”
Section: Discussionsupporting
confidence: 59%
“…But they ignored the impact of its concrete characteristics, such as the size, position, gestational age at diagnosis, duration or the simultaneous presence or absence of vaginal bleeding [2], [50], [51]. Even though many studies compared the symptoms in relation to the pregnancy complications, most of them were limited or small uncontrolled series, including without a clear definition of hematomas’ type and poor classification criteria as mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Women reporting moderate to heavy bleeding had more than twice the rate of spontaneous abortion compared with those reporting light bleeding (24.1% versus 9%; P = .003). They also reported, however, that 75% of women with heavy bleeding continued the pregnancy to viability 3 …”
Section: Vaginal Bleeding In the First Trimestermentioning
confidence: 99%
“…The amount of bleeding, along with other symptoms such as pain, identifies the urgency of the visit and contributes to the signs and symptoms that are considered part of a differential diagnosis. In a recent prospective study of 370 women with a positive pregnancy test and vaginal bleeding, the authors defined light bleeding as lighter than a period, moderate bleeding as similar to a period, and heavy bleeding as heavier than a period 3 . Women reporting moderate to heavy bleeding had more than twice the rate of spontaneous abortion compared with those reporting light bleeding (24.1% versus 9%; P = .003).…”
Section: Vaginal Bleeding In the First Trimestermentioning
confidence: 99%
See 1 more Smart Citation